The many colors of prominence: a pilot study of topic prosodic units - Erickson, Donna; Raso, Tommaso; Lundmark, Malin Svensson; Frid, Johan; Coulange, Sylvain (Journal of Speech Sciences, 2025)
This paper examines prominence from a pragmatic, phonological and acoustic-articulatory perspective. Based on results of a corpus-based analysis of Topic prosodic units in four languages (Italian, Brazilian and European Portuguese, and American English), three types of topic prosodic forms (TPFs) are described. Also are reviewed studies reporting phonological organization of English prominence patterns, as well as acoustic and articulatory characteristics of prominence, i.e., broad focus, narrow focus and emphasis, and specifically, how jaw lowering increases with increased prominence. Topic prominence has its scope on the whole prosodic unit, while narrow focus/emphasis prominence has its scope on one word. To examine the acoustic and articulatory characteristics of global prominence in a Topic prosodic unit compared with local prominence when the final topic word is emphasized, a pilot study of TPFs as spoken by an American English speaker was done. The results suggest that global Topic prominence differs from that of marking narrow focus/emphasis; narrow focus/emphasis prominence and Topic prominence are two different types of prominences both from the acoustic-articulatory and from the functional point of view. A new articulatory finding is that only for local prominence, i.e., when the topic word is emphasized, does the jaw show the largest amount of lowering in the phrase; for global prominence, the largest amount of jaw lowering occurs on another word within the phrase, not on the final topic word. Our findings, thus, suggest that there are different types of prominences whose functional values are reflected in the formal cues that implement them.